2021
DOI: 10.1136/bmjgh-2021-006653
|View full text |Cite
|
Sign up to set email alerts
|

Is the cure really worse than the disease? The health impacts of lockdowns during COVID-19

Abstract: Contributors All authors contributed equally to writing, editing, refining and improving the document as well as all literature searching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 33 publications
2
59
0
Order By: Relevance
“…However, social media also comprised discussions of how changes to young people’s social environments resulting from the pandemic had improved their mental health. Therefore, our findings align with recent research that has argued that COVID-19 control measures have had no singular or universal impact on individuals’ mental health [ 31 , 32 ]; the impact has been complex, nuanced and contextual.…”
Section: Discussionsupporting
confidence: 90%
“…However, social media also comprised discussions of how changes to young people’s social environments resulting from the pandemic had improved their mental health. Therefore, our findings align with recent research that has argued that COVID-19 control measures have had no singular or universal impact on individuals’ mental health [ 31 , 32 ]; the impact has been complex, nuanced and contextual.…”
Section: Discussionsupporting
confidence: 90%
“…In Vietnam a fourth wave has occurred. Even in the public health literature, calls have been made to moderate the containment measures in order to protect livelihoods, food security, and wellbeing ( Adams et al, 2021 ; Meyerowitz-Katz et al, 2021 ). For example, Rwanda and Vietnam have been rightly praised for exemplary containment of COVID-19 ( Karim et al, 2021 , Van Tan, 2021 ), but during the periods of stringent restrictions, we observed severe food insecurity outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Some major factors which contribute to specificity of pandemic anxiety are the fear of becoming infected and dying, socially disruptive behaviors, and adaptive behaviors (Asmundson and Taylor, 2020 ; Bernardo et al, 2020 ; Wang et al, 2020 ). In other words, the increased risk of death (Aldridge et al, 2020 ), additionally unemployment and economic losses (Coibion et al, 2020 ), and numerous restrictions introduced by the countries' governments around the world, lead to negative health consequences (Meyerowitz-Katz et al, 2021 ), that include pandemic anxiety with its specifics as well (Bernardo et al, 2020 ). Accordingly, a fair number of studies have been published indicating an increase in anxiety symptoms in pregnant women during the COVID-19 pandemic (Ayaz et al, 2020 ; Corbett et al, 2020 ; Durankuş and Aksu, 2020 ; Kotabagi et al, 2020 ; Lebel et al, 2020 ; Moyer et al, 2020 ; Saccone et al, 2020 ; Wu et al, 2020 ; Yue et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%